Evidence for exercise therapy in the treatment of depression and anxiety - Jan, Knapen (International Journal of Psychosocial Rehabilitation, 2013)
There has been over 25 years of systematic investigation examining the relationship between physical activity, especially aerobic exercise and weight training, and depression and anxiety. In this chapter, we first present the findings of the two most recent meta-analyses in the area of physical activity and depression and anxiety. Potential mechanisms by which exer- cise may reduce depression and anxiety are described. Depression and anxiety are associated with a high incidence of co- morbid somatic illnesses, especially cardiovascular diseases and type 2 diabetes. Positive effects of regular exercise on these diseases in individuals with depression and anxiety disorders are discussed. Finally, we offer evidence based recom- mendations for good clinical practice.